1978
DOI: 10.1007/bf01912397
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic parameters

Abstract: The wide variations of calculated activation energies for solid decomposition suggests that there is no discrete activated state. Further, the statistical distribution on which the calculations are based is not a realistic concept. The lowest energy possible --and most frequently occurring --is the energy of the bulk crystal. Within the crystalline solid, vibrational interactions transfer energy so rapidly that a substantial difference from the average energy is not achievable within the crystal. The lack of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Such reactions may be formally regarded as termolecular, or even higher molecularity, processes, which have negligible probabilities in gaseous encounters, but are possible, in principle, on a densely occupied surface. Second, Garn [42,43] has concluded that the energy distribution function for solids is different from that expressed by the Maxwell-Boltzmann equation, so that the Arrhenius equation, and mechanistic conclusions based on this approach, may be inapplicable. The same argument may be applicable to surfaces.…”
Section: From the Arrhenius Equation And Eq (3) It Follows Thatmentioning
confidence: 97%
“…Such reactions may be formally regarded as termolecular, or even higher molecularity, processes, which have negligible probabilities in gaseous encounters, but are possible, in principle, on a densely occupied surface. Second, Garn [42,43] has concluded that the energy distribution function for solids is different from that expressed by the Maxwell-Boltzmann equation, so that the Arrhenius equation, and mechanistic conclusions based on this approach, may be inapplicable. The same argument may be applicable to surfaces.…”
Section: From the Arrhenius Equation And Eq (3) It Follows Thatmentioning
confidence: 97%
“…It was noted in [ 15,38] that the Arrhenius law can hardly be used for solid-phase reactions; nevertheless, it is usually satisfied, since the unit chemical changes of which the total process is composed are of an activation nature. Just as in homogeneous processes, it is advisable to take into account the pre-exponent temperature-dependence [82].…”
Section: Nonisothermai Conditionsmentioning
confidence: 99%
“…Although interesting approaches to the problem have been found of late [14], on the whole there is no satisfactory theory to explain the activation energy and pre-exponential factor as applied to solid-phase reactions. According to [ 15], the decomposition of solids does not give rise at all to a discrete activated state, and the absence of statistical energy distribution precludes the use of the Arrhenius equation. One may hope that the analysis of isoparametric relations in the kinetics of reactions in solids will promote progress in this field, just as it has in the kinetics of homogeneous reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is uncertain which part of the thermal effect is connected with the phase transformation and can be used for kinetics computing, and which part is connected with other phenomena such as heat transition. Thus, DTA is still of questionable validity, because a representative value which would unambiguously define the change in the system is not available from the DTA peak [3]. The following question may be posed: if the kinetic parameters obtained from DTA measurements can be explained analogously as for homogeneous reactions, then do these parameters have any physical sense at all?…”
mentioning
confidence: 99%
“…The procedure most often used is to obtain the 9 factor on the basis of the increase in area of the DTA effect. However, the shape of the thermal effect is a function not only of the reaction kinetics, but also of the geometry and thermal diffusivity within the furnace, sample and thermocouple assembly [1][2][3]. It is uncertain which part of the thermal effect is connected with the phase transformation and can be used for kinetics computing, and which part is connected with other phenomena such as heat transition.…”
mentioning
confidence: 99%